Dorsomedial and ventromedial prefrontal cortex lesions differentially impact social influence and temporal discounting - Su, Zhilin; Garvert, Mona M.; Zhang, Lei; Vogel, Todd A.; Cutler, Jo; Husain, Masud; Manohar, Sanjay G.; Lockwood, Patricia L. (PLOS Biology, 2025)
The medial prefrontal cortex (mPFC) is involved in economic and social decision-making in humans but the specific functions of its subregions are not clear. This study shows that the dorsal mPFC is causally implicated in susceptibility to social influence, while the ventral mPFC is involved in temporal discounting.